Wheat genotypes with higher yield sensitivity to drought overproduced proline and lost minor biomass under severer water stress - Zhang, Xinying; Wang, Zhenzhao; Li, Yuzhong; Guo, Rui; Liu, Enke; Liu, Xiaoying; Gu, Fengxue; Yang, Ziguang; Li, Shuying; Zhong, Xiuli; Mei, Xurong (Frontiers in Plant Science, 2022)
To clarify the differences in growth and yield responses to drought stress among genotypes contrasting in environmental background, dryland and irrigated genotypes, as well as the underlying biochemical mechanism would provide valuable information for developing superior dryland cultivars. Pot experiments for the whole life cycle in fifteen genotypes and comparative metabolomics analysis for seedlings between two drought tolerant (DT) dryland genotypes and two drought sensitive (DS) irrigated ones were carried out. The DT dryland genotypes suffered heavy biomass loss during severer drought but showed minor yield loss ultimately, while the DS irrigated ones showed minor biomass loss but greater yield loss. Additionally, the superior DT dryland genotypes showed better yield performance under both drought stress and well-watered conditions, indicating their possessing both drought tolerance and high yield potential traits. Suffering severer drought stress, seedling leaves of the DS irrigated genotypes increased some amino acids and organic acids to maintain cell metabolism and accumulate more biomass. Proline in particular was overproduced, which might cause toxicity to cell systems and lead to enormous yield loss ultimately. In contrast, DT dryland genotypes increased the beneficial amino acid and phenolic acids to enhance cell self-protection for alleviating drought damage and efficiently minimized yield loss ultimately.